2013
DOI: 10.1063/1.4823732
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing surface-enhanced Raman scattering sensitivity of surfactant-free Ag-Fe3O4 nanocomposites through optimization of silver nanoparticle density and magnetic self-assembly

Abstract: Magnetic composite nanomaterials consisting of more than two functional constituents have been attracting much research interests due to the realization of multiple functionalities in a single entity. In particular, integration of ferromagnetic oxides and noble metal nanoparticles (NPs) in composites results in simultaneous magnetic activity and optical response where the optical property of the whole system could be modulated by application of an external magnetic field. In this work, we prepared Ag NPs-coate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…[36,51] However,our experiments showed that light scattering and absorption in the plasmonic spot could be detrimental to SERS analysis, if ac ritical NP concentration threshold was exceeded in the solution depositedfor the magnetic assembly. In this way,w eo bserved a2 8-foldi ncrement of the SERS signal collectedf rom the plasmonic spots, relative to the same NPs spotted on the glass slide without magnetic assembly or to ar eference of nonmagnetic pure Ag NPs.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…[36,51] However,our experiments showed that light scattering and absorption in the plasmonic spot could be detrimental to SERS analysis, if ac ritical NP concentration threshold was exceeded in the solution depositedfor the magnetic assembly. In this way,w eo bserved a2 8-foldi ncrement of the SERS signal collectedf rom the plasmonic spots, relative to the same NPs spotted on the glass slide without magnetic assembly or to ar eference of nonmagnetic pure Ag NPs.…”
Section: Discussionmentioning
confidence: 83%
“…[36] Interestingly,t heses ubstrates are achievable in ar eproducible ands calable way,a llowing the preparation of arrays of variable dimensions (varying the The widespreada pplication of surface-enhanced Raman scattering (SERS) would benefit from simple and scalable self-assembly procedures for the realization of plasmonic arrays with ah igh density of electromagnetic hot-spots. [51] In recent years,l aser ablation in liquid (LAL) has emerged as ar eliable approachf or the preparation of magnetic and plasmonic NPs in one step, even with unconventional structures or thermodynamically inhibited compositions. The use of laser ablation in liquid is key to achieving bimetallic NPs in one step with ac lean surface availablef or functionalization with the desired thiolated molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Because this situation causes the interference signal due to SERS of surfactant molecules, the surfactant-free synthesis of nanoparticles is an important issue in SERS application (Bao et al 2013). We prepared Ag nanoparticles suitable for SERS measurement and optical trapping by an original synthesis method without surfactant.…”
Section: Sers Detection Of Biomolecules With Optical Trapping Of Ag Nmentioning
confidence: 99%
“…Because this situation causes the interference signal due to SERS of surfactant molecules, the surfactant-free synthesis of nanoparticles is an important issue in SERS application (Bao et al 2013). Because this situation causes the interference signal due to SERS of surfactant molecules, the surfactant-free synthesis of nanoparticles is an important issue in SERS application (Bao et al 2013).…”
Section: Sers Detection Of Biomolecules With Optical Trapping Of Ag Nmentioning
confidence: 99%